2011
DOI: 10.1093/czoolo/57.6.717
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite variability reveals high genetic diversity and low genetic differentiation in a critical giant panda population

Abstract: Understanding present patterns of genetic diversity is critical in order to design effective conservation and management strategies for endangered species. Tangjiahe Nature Reserve (NR) is one of the most important national reserves for giant pandas Ailuropoda melanoleuca in China. Previous studies have shown that giant pandas in Tangjiahe NR may be threatened by population decline and fragmentation. Here we used 10 microsatellite DNA markers to assess the genetic variability in the Tang

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Only 31 individual giant pandas were identified from the 34 fecal samples: 16 from the Hongshihe subpopulation and 15 from the Motianling subpopulation ( Table 1 ). GIMLET analysis demonstrated that the combination of the 10 chosen loci produced identical genotypes of full siblings by chance with a probability of 2.4×10 −5 , which is consistent with the report by Yang et al [11] .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Only 31 individual giant pandas were identified from the 34 fecal samples: 16 from the Hongshihe subpopulation and 15 from the Motianling subpopulation ( Table 1 ). GIMLET analysis demonstrated that the combination of the 10 chosen loci produced identical genotypes of full siblings by chance with a probability of 2.4×10 −5 , which is consistent with the report by Yang et al [11] .…”
Section: Resultssupporting
confidence: 90%
“…Due to the poor quality of fecal DNA, only 34 out of the 91 fecal samples were successfully performed for individual identification with the 10 microsatellite loci under the methods of Yang et al [11] and Solberg et al [12] . Only 31 individual giant pandas were identified from the 34 fecal samples: 16 from the Hongshihe subpopulation and 15 from the Motianling subpopulation ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that low genetic variation was unlikely to be a critical threat to this species. With the improvement of noninvasive genetic sampling Fang et al 1996;Ding et al 1998;Zhan et al 2006), genetic studies in wild panda populations based on large-scale faecal collections were rapidly implemented, and these studies also detected relatively high levels of microsatellite and mtDNA diversity He et al 2008;Hu et al 2010a,b;Yang et al 2011;Zhu et al 2011b) (Table 1).…”
Section: Genetic Diversitymentioning
confidence: 99%